A unique dysprosium selenoarsenate(iii) exhibiting a photocurrent response and slow magnetic relaxation behavior. Issue 2 (7th December 2016) - Zhou, Jian; Zou, Hua-Hong; Zhao, Rongqing; Xiao, Hong; Ding, Qingran
Abstract : A unique dysprosium selenoarsenate(iii ) contains large oligomeric cluster [As3 Se6 ] 3− anions with binuclear dysprosium complexes as counterions, and exhibits a photocurrent response and slow magnetic relaxation behavior. Abstract : A redox, substitution and self-assembly reaction offers a novel dysprosium selenoarsenate(iii ) with As 3+ [Dy2 (tepa)2 (μ2 -OH)2 Cl2 ]3 [As3 Se6 ]2 (1, tepa = tetraethylenepentamine), which provides the first example of chair conformation ring [As3 Se6 ] 3− combined with lanthanide complexes as counterions.1 exhibits a photocurrent response and slow magnetic relaxation behavior.